The position of the Iranian press on the internal developments in Iran 1918-1925 AD in the light of Persian documents, a study in models - Aladdin al-Hakim; Ahmed Alalaq (آداب الكوفة, 2016)
Enjoyed the press and those who made it in Iran a kind of relative freedom during the first phase of old and evolved that movement during the years of the Constitutional Movement, and increased confidence and maturity during the years of the First World War, where the split itself between supporters and opponents of the foreign presence in Iran